Development and evaluation of the usability of a mobile application for electronic registration of pre-hospital emergency care (Research, Society and Development, 2021)
The article describes the developing and validating process of a mobile application for pre-hospital emergency care electronic registration. We carried out a cross-sectional technological assessment study, using a descriptive design and a quantitative analytical approach. The researcher built the mobile application following the software engineering phases: requirements analysis, design and specification, construction, internal testing, maintenance, and external evaluation. We use the System Usability Scale (SUS) instrument to evaluate the mobile application. The study sample consisted of 25 participants: 15 pre-hospital care (PHC) professionals, registered nurses, licensed practical nurses working at the SAMU in São José do Rio Preto, and 10 Information Technology (IT) professionals. As a result of the validation, the APH Mobile application met the criteria of ease of learning the system (77.92) ± 0.09, system efficiency (75.76) ± 0.03, ease of memorization (66.67), minimization errors (76.67), and user satisfaction (84.44) ± 0.06. The application's SUS score of 76.67 ± 17.57 demonstrated that the application meets usability requirements. The application can increase the efficiency of information processing through a more immediate data collection, enabling data analysis and resulting in assistance and management gains, resulting from the availability of comprehensive, accurate, and timely information.